Health Believe Model Implementation on The Analyze of Family Decision to Visit The Public Health Center - Purwaningsih Purwaningsih; Ni Ketut Alit Armini; Susanti Susanti (Universitas Airlangga, 2009)
Introduction : Dengue Haemorhagic Fever (DHF) is one of infecsius deseases. These deseases can have serious complications and kill the patients. Dengue Haemorhagic Fever (DHF) deseases that is suffered to the patients has become a heavy complication in Tembok Dukuh village. By the health belief model implementation, the patients got earlier response as soon as possible. The objective of the study was to analyze family’s decision for visiting Puskesmas in earlier response of Dengue Haemorhagic Fever (DHF). This descriptive analytic was conducted at work area of Puskesmas Tembok Dukuh Surabaya. The population was the family with Dengue Haemorhagic Fever (DHF) patient from Januari 2007 until July 2009.Methods : Clustered design was used to take the sample. Total sample were 65 respondents, taken according to inclusion criteria. The independent variables were health belief model about perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers, and cues to action. The dependent variable was family’s decision for visiting Puskesmas in earlier response of Dengue Haemorhagic Fever (DHF). Data was collecting using structured questionnaire. Data that had collected were later analyzed with frequency distribution of each category.Results : Result showed that perceived susceptibility most family was in middle category, perceived seriousness most family was in high category, most of family got the benefits, most of family also got the barriers, and all of the respondents have cues to action. The family’s decision to visit Puskesmas for the earlier Dengue Haemorhagic Fever (DHF) response was founded in a few of family.Conclusion: It can be concluded that most of the family didn’t have a steady decisison to visit Puskesmas for the earlier Dengue Haemorhagic Fever response. It can be proved by there are most of family chose the others health service. Discussion : Health workers in Desease Eradication Departement (P2M) should sosialize the Puskesmas program related with the earlier Dengue Haemorhagic Fever (DHF) response. So that, the family has believed that visiting Puskesmas is important for the earlier Dengue Haemorhagic Fever (DHF) response.